Translation as cultural diplomacy: a Chinese perspective. Issue 7 (10th November 2021) - Jiang, Mengying
ABSTRACT: The People's Republic of China, since its foundation in 1949, has been at the forefront of strategizing outward translation (translation of works for readers outside of China) as a means of cultural diplomacy. The concept ' guojia fanyi shijian ' (literally, national translation practice) is being developed by Chinese scholars to analyze state-sponsored translation. This article provides a historical overview of China's state-sponsored outward translation activities and aims to highlight the conundrum of deploying translation as a means of cultural diplomacy in the Chinese context. The close relationship between the concept of soft power and the Chinese propaganda system not only constrains the creativity and attractiveness of cultural resources, but also predisposes translation projects to prioritize the source culture over the target culture. Based on the possibility of extending cultural diplomacy beyond national interests, this article argues that the Chinese government's use of translation for cultural diplomacy should draw insights from intercultural communication practices to reinvent the principle of ' neiwai youbie ' (different approaches to domestic and foreign propaganda work). In particular, the growing international popularity of Chinese online literature, largely translated by fans, is a timely reminder for policymakers to reform their conventional translation policies with the aim of increasing soft power.